2020
DOI: 10.1186/s43046-019-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar cancer: surgical management and survival trends in a low resource setting

Abstract: Background: This study aims to analyze risk factors, clinical profiles, treatment protocols, and disease outcomes in histologically proven resectable vulvar cancer (VC) patients according to tumor stage. This is a retrospective analysis of a prospectively collected database of 20 VC patients from May 2014 to June 2019. Results: The mean age of VC diagnosis was 55 years, with a range of 38-84 years. The incidence was four cases per year. The disease incidence was significantly more in post-menopausal (65%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…Subsequently, Modi et al 20 showed the 2-year disease-free survival was 100% in those with no nodal involvement, 73.5% in those with unilateral nodal disease, and only 60% in those with bilateral nodal involvement. 16 The mean overall survival in our study was 61.65 months for all stages which was comparable with the studies by other authors ie, Kumar et al 11 and Singh et al 12 For patients who did not undergo GND or postoperative radiation therapy, we could not assess them for their nonrecurrence or survival, although the tumor size was more than 2 cm with a depth of stromal invasion . 2 mm.…”
Section: Discussionsupporting
confidence: 89%
“…Subsequently, Modi et al 20 showed the 2-year disease-free survival was 100% in those with no nodal involvement, 73.5% in those with unilateral nodal disease, and only 60% in those with bilateral nodal involvement. 16 The mean overall survival in our study was 61.65 months for all stages which was comparable with the studies by other authors ie, Kumar et al 11 and Singh et al 12 For patients who did not undergo GND or postoperative radiation therapy, we could not assess them for their nonrecurrence or survival, although the tumor size was more than 2 cm with a depth of stromal invasion . 2 mm.…”
Section: Discussionsupporting
confidence: 89%
“…Eke et al also found highest incidence of vulvar cancer in low socio-economic class. 12 Most (56.3%) of patients were postmenopausal which is nearly similar to the study conducted (70%) by Meelapkij et al 14 About 67.7% participants were married and 24.0% patients were widowed in the current study. Huang et al found 42.1% patients to be married and 25.2% patients widow in their study, which is also comparable to present study.…”
Section: Discussionsupporting
confidence: 87%
“…It is almost in contrary to an Indian study conducted by Kumar et al where the patients were mostly Hindu (90.0%) followed by Muslims (5.0%) and Christian (5.0%). 12 This is because of the religious preponderance of the population of particular geographical areas. Study population mostly belonged to low socio-economic class and was illiterate (58.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies describing the local landscape of cancer surgery burden, caseload, operative techniques, outcomes, and barriers are foundational to identifying key intervention targets and to evaluating change over time. 15,16 On a more "microscopic" level, recent studies highlighting differences in tumor pathology and epidemiology between settings have yielded important insights. [17][18][19][20][21] A study among Indian patients status-post radical cholecystectomy for gallbladder carcinoma supported the utility of evaluating lymph node involvement for determining prognosis.…”
Section: Local Epidemiologic Studiesmentioning
confidence: 99%